Increasing the interlayer strength of 3D printed concrete with tooth-like interface: An experimental and theoretical investigation. (November 2022) - He, Lewei; Li, Hua; Chow, Wai Tuck; Zeng, Biqing; Qian, Ye
Graphical abstract: Highlights: Improvements of interlayer tensile strength by 291% and shear strength by 89% are achieved by interface tooth angle of 45°. Interlayer strength is theoretically modeled by tooth angle, void ratio, and the ratio between adhesion and cohesion. Validation is conducted with a relative error of about 5% and the strengths decently included in the prediction envelope. Within 5-min interval, voids decrease the interlayer strength notably. Otherwise, adhesion degradation is more impactful. Abstract: In 3D concrete printing, layer interface and interlayer notch are generated by the layer-by-layer process. Therefore, the 3D printed concrete is anisotropic with the interlayer strength lower than the strengths measured in the other two directions. In order to adequately address this issue, tooth-like layer interface is adopted in the present study for higher interlayer strength. It is found that the tooth-like interface with tooth angle of 45° increases the interlayer tensile and shear strengths by 294% and 89% respectively, and shifts the failure mode from pure adhesive failure to a mixture of adhesive and cohesive failures. Moreover, a theoretical model is developed for the relationship between the interlayer strength and interfacial tooth angle, and then validated by the experimental data with a relative error of about 5%. By this model, further design and optimization of the interfacial geometry would be possible, for higher interlayer strength subject to different parameters and conditions of 3D concrete printing.